The Influence of Brand Ambassador (Treasure) and E-WOM on Purchase Intention through Brand Image on the Ruangguru Application in High Schools - Kojongian, Marcellino Kevin; Suleman, Dede (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
In the current era of digitalization, many phenomena often appear in Indonesia, such as the transformation of the learning system in education that uses technology and internet media more. Today's young Indonesians like South Korean culture which is synonymous with K-pop. The emergence of new habits from today's consumers is to share their experiences online more often in the form of reviews, testimonials, and content. Consumer behavior today is also difficult to predict in purchasing because some consumers tend to buy products or services only based on their brand image and not their functional value. For this reason, this study aims to analyze and test how much influence Brand Ambassador and E-WOM have on Purchase Intention through Brand Image with a population of high school students in South Tangerang who are interested in Ruangguru. This study uses quantitative methods with a descriptive approach and analytical techniques using SEM-PLS with SMART-PLS applications. The results of this study have 243 respondents whose data has been processed and has met the requirements in the study. The statistical test results show that Brand Ambassadors have a significant and positive effect on Purchase Intentions, Brand Ambassadors have a positive and significant effect on Brand Image, E-WOM has a positive and significant effect on Purchase Intentions, E-WOM has a positive and significant effect on Brand Image, Brand Image has a positive and significant impact on Purchase Intentions, then the Brand Ambassadors and E-WOM have an indirect influence on Purchase Intention through Brand Image.